Generation of a predictive test for the diagnosis of the etiology of variceal upper gastrointestinal bleeding - Pérez-Condori, Luis Yasser (2023)
Our objective was to develop a diagnostic test to predict the etiology of Variceal Upper Gastrointestinal Bleeding (VUGIB). We conducted a retrospective cohort study. Medical records of patients over 18 years of age with Upper Gastrointestinal Bleeding (UGIB) who attended the emergency service of Hospital Cayetano Heredia (HCH) in Lima-Peru between 2019 and 2022 were reviewed; demographic, laboratory and clinical data were collected. Subsequently, predictive variables of variceal upper gastrointestinal bleeding (VUGIB) were identified using multiple logistic regression. Each variable with predictive capacity was assigned a score with a cut-off point and served to build a predictive scale for VUGIB. 197 medical records of patients with UGIB were included, of which 127 (64%) had non-variceal bleeding, and 70 (36%), variceal. Four independent predictors were identified: hematemesis (red vomit) (OR: 4,192, 95% CI: 1.586-11.082), platelet count (OR: 3.786, 95% CI: 1.324-10.826), history of UGIB (OR: 2.634, 95% CI: 1.017-6.820), signs of chronic liver disease (OR: 11.244, 95% CI: 3.067-35.047), with which a predictive scale was constructed, with a cut-off point >7 and ≤7; which showed a sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative of 58.6%, 90.6%, 77.4%, 79.9%, 6.20, and 0.46 respectively. In conclusion, the predictive scale with a cut-off point >7 is useful for predicting the presence of VUGIB in patients who attend the emergency room for UGIB.